KEPENTINGAN POLITIK JEPANG ATAS PEMBERIAN BANTUAN ODA UNTUK INDONESIA PASCA BENCANA GEMPA DAN TSUNAMI JEPANG 11 MARET 2011 - Taufan Himawan (2012)
Japan as one of the great economy leader countries in the world has suffered loss so much during triple disaster (earthquake, tsunami, nuclear radiation) occurred on March 11th 2011. However, one of their foreign policy through developing countries, ODA (Official Development Assistance), still continues and seems there is no sign to stop or even decrease the amount of provision used to give. In this case, it is about Japan's ODA for Indonesia. As we know that the diplomatical relationship betwee